Interaction of smoking and metabolic syndrome on cardiovascular risk in a Chinese cohort - Zhang, Lijun; Guo, Zhirong; Wu, Ming; Hu, Xiaoshu; Xu, Yanying; Zhou, Zhengyuan (International journal of cardiology, 2013)
The high prevalence of smoking and metabolic syndrome (MS) and increased incidence of cardiovascular disease (CVD) in China indicates that there may be an interaction between smoking and MS on cardiovascular risk. Therefore, we aimed to examine the independent and combined effects of smoking and MS on risk of CVD in a Chinese cohort. We analyzed data from a population-based prospective cohort of 3598 participants aged 35–74years from Jiangsu China who were free of diabetes and CVD at enrollment and were followed for cardiovascular events (including myocardial infarction, ischemic stroke, hemorrhagic stroke, and cardiovascular mortality) until 31 August 2008. During 8years (median 6.3years) of follow-up, 82 participants developed CVD. After adjusting for age, sex, body mass index, alcohol consumption, family history of cardiovascular disease and MS, smoking significantly increased cardiovascular risk in a dose–response manner. After further adjustment for smoking status, the hazard ratio of CVD for participants with MS was 2.49 (95% confidence interval 1.59–3.90) compared with those without the syndrome. There was a statistically significant additive interaction between current smoking and MS on cardiovascular risk. The risk of CVD for current smokers with MS was 1.81 times as high as the sum of risks in participants with a single condition alone. Both cigarette smoking and MS are strong risk factors of CVD in the Chinese population. Moreover, this study further demonstrates an additive interaction of current smoking and MS on cardiovascular risk.